Tout le reste n’est pas que roman… : Inflexions et convergences dans la poésie française post-80 - Coutinho, Ana Paula (2018)
Does french poetry written and published after the 1980's correspond to a disruption or to a re-appropriation of certain axes of aesthetic modernity? Even if in a provisional and brief way, the reading proposed here will try to answer this question, highlighting the structuring lines regarding the literature that marks the transition between the twentieth- and the twentyfirst century.